Mucopolysaccharidosis and organ of sight - Modrzejewska, Monika; Kot, Joanna; Wiśniewska, Agnieszka; Romanowska, Hanna; Giżewska, Maria (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
Mucopolysaccharidoses are a group of genetically determined storage diseases in which lysosomal enzyme deficiency leads to a vast accumulation of glycosaminoglycans in tissues. Depending on the sort of deficient enzyme MPS are divided into the types marked with Roman numerals. Clinical symptoms are caused by the involvement of the nervous, respiratory, visceral and skeletal system, organ of hearing and sight. Ocular manifestations result in significant visual impairment. Ophthalmic symptoms include corneal opacification, glaucoma, optic nerve swelling and retinopathy. Modern methods for the treatment involving enzyme replacement therapy and bone marrow transplantation significantly improved the prognosis in many cases. This article presents a brief description of mucopolysaccharidoses, concentrating mainly on ocular symptoms and their possible treatments.